Trends and Prospects in Geotechnics - da Venda Oliveira, Paulo José; Correia, António Alberto Santos (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue book presents some works considered innovative in the field of geotechnics and whose practical application may occur in the near future. This collection of twelve papers, in addition to their scientific merit, addresses some of the current and future challenges in geotechnics. The published papers cover a wide range of emerging topics with a specific focus on the research, design, construction, and performance of geotechnical works. These works are expected to inspire the development of geotechnics, contributing to the future construction of more resilient and sustainable geotechnical structures.